Moving. (22nd December 2017) - Gill, Sam
Abstract : Identifying hope and redemption with moving and vitality, the dystopian film Mad Max: Fury Road surprisingly inspires us to develop the implications of moving as the core of religion. For animate organisms life is synonymous with self-moving. Philosophy and biology connect moving with not only vitality, but also with experience, perception and conception. Hope and redemption are qualia of human living. Enduring academic standards tend to halt the moving richness of religions. Taking as radically as possible the primacy of self-moving, an alternative is presented that prefers kinesiology to autopsy. Seven propositions are developed, directed especially to the emerging generation of religion scholars.